OC-050 Inpatient paediatric UC care in the UK in 2011 is characterised by increasing rates of rescue therapy and stool cultures but low use of pucai scores. (28th May 2012) - Russell, R K; Protheroe, A; Roughton, M; Croft, N; Murphy, M S; Spray, C; Rodrigues, A; Wilson, D C; Puntis, J; Cosgrove, M; Tarnock, A; Rao, P; et al.
Abstract : Introduction: Paediatric UC care is variable in the UK and appropriate clinical guidelines are very recent. Acute severe UC is rare with only a few cases presenting annually to each tertiary hospital. Methods: UC patients aged <17 years admitted to 23 UK paediatric hospitals had clinical details collected as part of the UK paediatric IBD audit (September 2010–2011). Each site was asked to enter up to 20 cases admitted electively or as an emergency, including patients who were having surgery. Day cases and patients who were admitted solely for diagnostic endoscopy were excluded. Comparative data for some items was available from the previous UK audit conducted in 2008. Results: 176 patients (98 males) of median age 13 years (IQR 10–13) were included in the audit; 22 were elective surgical admissions, 47 new diagnoses and 107 needed acute medical care for known UC. Median length of stay was 6 days (IQR 3–10); there were no deaths. 73% of patients with established disease had a pancolitis and 10% had co-existent liver disease. 88 (70%) of 126 patients with active disease had standard stool cultures performed (2% were positive) and 57 (45%) had C difficile toxin tested (none positive). Stool sample collection rates had improved significantly compared to the 2008 audit (70% vs 52%, p=0.001). 38% of emergency admissions had a plain abdominal XR taken on admission, but only 19% had a specific disease activity index (PUCAI score) recorded. There were three cases of toxic megacolon and 3 of thromboses. Rates of heparinisation were low but higher than in the 2008 audit (11% vs 2%, p=0.002). 71% of patients treated with steroids responded to treatment. 20 patients received 2nd line (rescue) therapy, of whom eight received infliximab, 11 Cyclosporin and one both, with an overall response rate of 90%; nine went to surgery without 2nd line medical therapy. Rescue therapy usage was significantly higher than in the 2008 audit (52% vs 26%, p=0.03). Overall, 71% of non-elective UC admissions were seen by an IBD nurse. Conclusion: There were signs of improving UC care from 2008 to 2011 with significantly increased rates of stool culture sampling and use of rescue therapy, but the majority of sites did not use PUCAI scores to assess patients on emergency admission. Competing interests: None declared.